ANALISIS MAJAZ DALAM SURAT YASIN: KAJIAN ILMU BAYAN - Muhammad Farhan Yazid Zidan Lubis; Raden Diaz (Jurnal Sathar, 2025)
This study aims to analyze the use of majaz in Surah Yasin verses 1–25 with the bayan science approach, as part of the balaghah science branch in the study of the language of the Qur'an. This study is important because the language of the Qur'an is known to have extraordinary depth of meaning and structural beauty. The method used is qualitative literature research, with primary data in the form of the text of the Qur'an and secondary data in the form of tafsir books and balaghah science references. The results of the study show that in verses 1–25 of Surah Yasin there are various types of majaz, such as mursal, isti'arah, kinayah, and tamtsil majaz. This style of language not only beautifies the verses of the Qur'an, but also strengthens the messages of da'wah which are invitations, warnings, and lessons for humanity. For example, the use of isti'arah in verse 8 describes the hardness of the hearts of the infidels, and tamtsil in verses 13–19 provides lessons about human response to the call of truth. This study concludes that bayan science is very helpful in exploring the hidden meaning behind the text of the Qur'an. Through this approach, it can be seen that the language of majazi plays an important role in conveying Islamic teachings in a subtle, profound, and touching way to the reader's feelings. Therefore, this kind of study needs to be continuously developed to enrich the understanding of the holy text of the Qur'an.